2012
DOI: 10.5551/jat.9639
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Ankle Vascular Index in Heterozygous Familial Hypercholesterolemia

Abstract: Aim:The cardio-ankle vascular index (CAVI) is a new non-invasive marker of arterial stiffness and atherosclerosis. The purpose of this study was to compare CAVI in patients with heterozygous familial hypercholesterolemia (FH) and in healthy controls. Methods: 82 FH subjects (27 males, 65 females), aged 53.7 13.6 years without clinical symptoms of cardiovascular diseases and 359 healthy controls (121 males, 238 females), aged 43.9 14.9 years, were examined. CAVI was measured using the system VaSera ® 1500. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
3
23
2
2
Order By: Relevance
“…Soska et al 42) showed that CAVI was not high in heterozygous familiar hypercholesterolemic patients. On the other hand, some reports showed that CAVI is related to low-density lipoprotein (LDL) cholesterol level and also to the cholesterol / high-density lipoprotein (HDL) cholesterol ratio 43) .…”
Section: (C) Dyslipidemiamentioning
confidence: 99%
“…Soska et al 42) showed that CAVI was not high in heterozygous familiar hypercholesterolemic patients. On the other hand, some reports showed that CAVI is related to low-density lipoprotein (LDL) cholesterol level and also to the cholesterol / high-density lipoprotein (HDL) cholesterol ratio 43) .…”
Section: (C) Dyslipidemiamentioning
confidence: 99%
“…This was consistent with the findings from the previous by Soska et al They compared CAVI in FH patients and in healthy controls. 33 There was no signi ficant difference in HDL-cholesterol levels between FH patients and the controls. 33 In our study, there was also no significant difference in HDL-cholesterol levels between patients with and without CAS, although LDL-cholesterol level was higher in patients with CAS.…”
Section: Multiple Regression Analysis Of Various Parameters For Casmentioning
confidence: 97%
“…33 There was no signi ficant difference in HDL-cholesterol levels between FH patients and the controls. 33 In our study, there was also no significant difference in HDL-cholesterol levels between patients with and without CAS, although LDL-cholesterol level was higher in patients with CAS. On the other hand, another study showed that a significant increase in CAVI was observed in patients with combined hyperlipidemia who had a low (,40 mg/dL) HDL-cholesterol level but not in patients with hypercholesterolemia alone.…”
Section: Multiple Regression Analysis Of Various Parameters For Casmentioning
confidence: 97%
See 1 more Smart Citation
“…The highest CAVI was found in the group of patients with increased LDLcholesterol as well as hs-CRP. Moreover, CAVI in patients with dyslipidaemia may be influenced also by treatment with hypolipidaemics 36,37) . It has been reported that statins decrease CAVI and improve arterial stiffness in patients with coronary artery disease and hyperlipidaemia 38,39) .…”
Section: Disclosurementioning
confidence: 99%